EFFECT OF PRE-HARVEST SPRAYS OF BIOSTIMULANTS ON POST- HARVEST VASE LIFE OF CUT GLADIOLUS CV. ARKA AMAR - RAVIKUMAR BOLAGAM; SEENIVASAN NATARAJAN (The Bioscan, 2020)
Gladiolus is one of the popular cut flowers that usually encounter postharvest problems resulting in shorter vase life and loss of quality. The present investigation was carried out at Floricultural Research Station, Rajendranagar, Hyderabad, during Rabi, 2017-18. The experiment was laid out in Completely Randomized Block Design replicated thrice, 5 biostimulant treatments were tried at two different concentrations. Significantly Humic acid at 4ml/L treatment i.e T8 recorded longer vase life (10.43 days), the lowest was recorded in control. Highest number of days taken for 50 and 100 per cent floret opening (4.63, 9.10 respectively), and also higher water uptake (18.20 g.spike-1) was recorded in HA treatment. The highest Transpirational loss of water was recorded in Fulvic acid at 4ml/L (18.45 g spike-1) and it was lowest in control. While, minimum percent of spoilage of floret (39.08 %) was recorded in humic acid at 4ml/L treatment. The results showed that pre soaking and foliar sprays with Humic acid at 4ml/L recorded significantly best results for almost all the postharvest and physiological parameters studied except for water balance. Hence, the same treatment was used to extending vase life, delay spike senescence and enhance post-harvest quality of cut gladiolus spikes.